The reconstruction of Holocene northwestern Mongolian fire history based on high-resolution multi-site macro-charcoal analyses - Unkelbach, Julia; Behling, Hermann (Frontiers in Earth Science, 2022)
In palaeoecology, multi-site macro-charcoal analyses provide information on climate-fire-vegetation linkages, their spatial and temporal extent as well as the impact of prehistoric human practices. Our multi-site study comprises 8 macro-charcoal records from two highly continental forest-steppe regions in Western and North-Central Mongolia covering the Holocene. In addition to reviewing macro-charcoal influxes and comparing macro-charcoal morphotype results with arboreal/non-arboreal pollen ratios, our dataset provides the first fire frequency synthesis for two regions in Mongolia. During the early and mid-Holocene, the fire history in Western and North-Central Mongolia is controlled by the regional climate variability, whereas the fire intensities are higher in the Mongolian Altai. In general, fire frequencies are lower in the Northern Khangai. Increases in the fire frequency correlate with the potential beginning of a rise in the nomadic population of the Mongolian Altai after 1100 cal yr BP. In both areas, individual macro-charcoal peaks, a marked site-to-site variability and a generally very low impact on the forest-steppe distribution may mostly be explained by a strictly local nomadic disturbance.